Neuropharmacological Activity of Nut Grass (Cyperus Rotundus L.) Rhizome Fraction - Dwita, Lusi Putri; Dewanti, Ema; Ladeska, Vera; Sediarso, Sediarso; Muntashir, Adnan; Safni, Ulfa; Sari, Rahma Wulan (Pharmaciana, 2018)
Research in the area of herbal neuropharmacological effects has increased markedly over the past decades. This research was aimed to further investigate neuropharmacological properties of Cyperus rotundus rhizomes fraction by measuring hypnotic-siccative and anticonvulsant activities. The exploratory behavior test was performed using Hole Board method while motor coordination was assessed using Rotarod Test. The result showed that the 70% ethanol fraction of Cyperus rotundus rhizome in has significant (p <0,05) neuropharmacological activities. All three fractions tested (ethanol, ethyl acetate, and n-hexane), the ethanol fraction showed the best hypnotic-sedative and anticonvulsant activities. Ethanol Cyperus rotundus rhizome fraction could decrease the duration of HLE equal to sodium valproate and potentiated the phenobarbital-induced sleep by decreasing the onset and prolonging the duration of sleep. The highest dose of 70% ethanol fraction of Cyperus rotundus rhizome (356.7 mg/kg) showed the best anxiolytic activity comparable to diazepam (p> 0.05). In conclusion, Teki ladang (Cyperus rotundus) rhizome appeared as potent neuropharmacological drug candidate with abilities comparable to synthetics drugs.Â